The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006 International Conference of the IEEE Engineering in Medicine and Biology Society 2006
DOI: 10.1109/iembs.2006.259678
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Large-Scale Brain Data for Brain-Computer Interfaces

Abstract: We present a systematic technique for extraction of useful information from large-scale neural data in the context of brain-computer interfaces. The technique is based on a direct linear discriminant analysis, recently developed for face recognition problems. We show that this technique is capable of extracting useful information from brain data in a systematic fashion and can serve as a general analytical tool for other types of biomedical data, such as images and collections of images (movies). The performan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 20 publications
1
8
0
Order By: Relevance
“…RLDA and CSP perform best on subjects S006 and S004, respectively, whereas DLDA and especially PLDA perform poorly. This is consistent with previous studies [29], [48], [50], where these and other face recognition techniques were found ill-suited for classification of noisy biomedical data. Also note that the computational cost of RLDA is an order of magnitude higher than those of the CPCA, PLDA, and CSP techniques.…”
Section: B Analysis Of Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…RLDA and CSP perform best on subjects S006 and S004, respectively, whereas DLDA and especially PLDA perform poorly. This is consistent with previous studies [29], [48], [50], where these and other face recognition techniques were found ill-suited for classification of noisy biomedical data. Also note that the computational cost of RLDA is an order of magnitude higher than those of the CPCA, PLDA, and CSP techniques.…”
Section: B Analysis Of Resultssupporting
confidence: 81%
“…Since spatiotemporal ECoG data are essentially an image, it may be worthwhile to cast a classification of ECoG data in the framework of image/face recognition. However, when applied to ECoG data, several representative face recognition techniques produced very modest results [29], [48], [50]. The discrepancy in performance may be attributed to relatively high levels of noise in electrophysiological neural data.…”
Section: B Classwise Principal Component Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…To obtain meaningful data statistics, this irrelevant subspace must be discarded as noise, which is typically accomplished by global dimensionality reduction [5], and variants thereof [9], [10], have been successfully used. However, our experience with face recognition techniques applied to brain data were somewhat disappointing [7]. Motivated by these limitations, we proposed a modification of the direct LDA (DLDA) method [9], by introducing a threshold [7], whose role was to regularize the covariance matrix in a manner similar to the standard shrinkage approach [11].…”
Section: Classwise Principal Component Analysismentioning
confidence: 99%
“…While the power/frequency representation is physically intuitive, it is unclear why these ad hoc features should have optimal predictive power. Several studies [6], [7], [8] report significantly better decoding results with the use of other (more abstract) features. Another common strategy, often used in conjunction with the above, is to rank individual features (or recording electrodes) according to some criterion.…”
mentioning
confidence: 99%